Ulysses - Joyce, James, 1882-1941 ([The Modern library of the world's best books], 1992)
Serialized first in the Little Review in 1918 and published first in Paris in 1922, although its censorship for obscenity in America and England were not lifted until the mid-1930s. In terms of its story it defies abridgement or explanation except that it all takes place on one day, 16 June 1904, or Bloomsday, which was the anniversary of Joyce's first walk with his beloved Nora Barnacle. It (very) loosely follows the episodes of Ulysses from the Odyssey of Homer though in a reordered form, with Stephen Dedalus representing Telemachus, Leopold Bloom Ulysses and Molly Bloom Penelope. The central characters explore various sites and happenings around Dublin such as a newspaper office, a brothel, a funeral, and public houses.